Manajemen Berbasis Sekolah dan Kesalahpahaman Persepsi - Soetam Rizky Wicaksono; Abdul Hakim; Kasmudin Mustapa (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
While SBM (School-Based Management) has already been implemented in many countries, including Indonesia, the Education Council has already brought this idea to create a better education act. However, SBM still has the wrong paradigm among principals of schools in Indonesia. Some of them still hardly believe that SBM can leverage their school. This paradigm is based upon their narrow-minded point of view because many of them feel that there is no "real example" that SBM really can do that is leverage from the promise. Therefore, this research tries to give empirical evidence that SBM in Indonesia can give leverage factors to schools. Even though SBM has been proven to leverage schools' achievement, there are still misperceptions among school management, parents, and teachers about how SBM should work. The result of this research is also being socialized to the principals, so they can understand how important SBM is for their school and will be eager to implement SBM in their school (for those who do not implement it yet).